Analisis terhadap Penerimaan Merek yang Digunakan sebagai Objek Jaminan Fidusia - Igal Gilang Kurniawan; Kadek Wiwik Indrayanti; Hendra Djaja; Muhammad Fahrial Amrullah (Bhirawa Law Journal, 2021)
In the context of national development amid the progress of the times, intellectual property in the form of brands is considered to have potential as a source of banking funding. Intellectual property in it resides in economic rights and moral rights so that it is believed to have commercial value so that it is very possible to be used as an object of collateral for banks to obtain credit facilities. In banking practice, trademark rights have been accepted as objects of fiduciary guarantees as additional guarantees to obtain credit facilities. Marks are specifically regulated through Law Number 20 of 2016 concerning Marks and Geographical Indications. However, the mark is not mentioned as an object that can be imposed on it using a fiduciary scheme. This study uses a juridical-normative approach. This research focuses on library materials such as laws and regulations and relevant sources. This study examines the basis of brand acceptance as an object of fiduciary guarantee and brand requirements as an object of fiduciary guarantee. The results of this study indicate that the brand is classified as an intangible movable object that has a valuation (economic value) in it that can be used as an object in a legal relationship. A mark can be imposed on it by using a fiduciary scheme if the mark meets the juridical requirements, its economic value can be measured reliably and does not conflict with the socio-cultural